Succession. The fourth and final season [videorecording (DVD)] - Armstrong, Jesse (Warner Bros. Entertainment Inc., 2023)
The sale of media conglomerate Waystar Royco to tech visionary Lukas Matsson looms ever closer, provoking existential angst and division among the Roys in the fourth and final season of Jesse Armstrong's Emmy-winning drama series. As the siblings anticipate the prospect of this seismic merger, the ensuing power struggle finds them grappling with what their lives will look like after the deal and weighing a future where their cultural and political capital is severely curtailed.